DETERMINANTS OF CORPORATE SUSTAINABILITY DISCLOSURE: EVIDENCE FROM ESG BOARD - Linda Ayu Wulandari; Hendro Paulus; Nita Erviana; Deden Tarmidi; Diah Iskandar (ZILLZELL MEDIA PRIMA, 2026)
Corporate sustainability disclosure (CSD) has become an important mechanism for improving transparency regarding corporate environmental and social responsibilities. This study examines the determinants of corporate sustainability disclosure by analyzing the roles of environmental commitment, circular economic initiatives, and firm size, as well as the moderating effect of financial risk. The study also compares sustainability disclosure practices between firms with Environmental, Social, and Governance (ESG) boards and those without. The sample consists of 185 firm-year observations from energy sector companies listed on the Indonesia Stock Exchange during 2020–2024. Panel data regression with moderated regression analysis was employed. The results indicate that environmental commitment affects sustainability disclosure differently depending on the presence of ESG boards. Meanwhile, circular economy initiatives and firm size positively influence sustainability disclosure regardless of governance structure. Financial risk strengthens environmental disclosure incentives but weakens the influence of firm size.